Incidental Findings on 18F-Fluorocholine PET/CT for Parathyroid Imaging - Wouter A.M. Broos; Remco J.J. Knol; Friso M. van der Zant; Nicolaas C. Schaper; Maurits Wondergem (World Journal of Nuclear Medicine)
Introduction 18F-choline positron emission tomography/computed tomography (PET/CT) is an upcoming imaging technique for the localization of hyperfunctioning parathyroid glands. However, 18F-choline is a nonspecific tracer that also accumulates in malignancies, inflammatory lesions, and several other benign abnormalities. The aim of this study was to determine the occurrence and relevance of incidental findings on 18F-choline PET/CT for parathyroid localization. Materials and Methods 18F-choline PET/CTs performed in our center for parathyroid localization from 2015 to 2019 were reviewed. Abnormal uptake of 18F-choline, with or without anatomical substrate on the co-registered low-dose CT and also incidental findings on CT without increased 18F-choline uptake were recorded. Each finding was correlated with follow-up data from the electronic medical records. Results A total of 388 18F-choline PET/CTs were reviewed, with 247 incidental findings detected in 226 patients (58%): 82 18F-choline positive findings with corresponding pathology on CT, 16 without CT substrate, and 149 18F-choline negative abnormalities on CT. Malignant lesions were detected in 10/388 patients (2.6%). Of all 98 detected 18F-choline positive lesions, 15 were malignant (15.3%), concerning 4 metastases and 11 primary malignancies: breast carcinoma (n = 7), lung carcinoma (n = 2), thyroid carcinoma (n = 1), and skin melanoma (n = 1). Conclusion Clinically relevant incidental findings were observed in a substantial number of patients. In 15.3% of the incidental 18F-choline positive findings, the lesions were malignant. These data contribute to better knowledge of 18F-choline distribution, enhance interpretation of 18F-choline PET/CT, and guide follow-up of incidental findings. Attention should especially be paid to breast lesions in this particular patient group with hyperparathyroidism in which women are typically over-represented.